Exploring The Use of Podcasts as Learning Media in Enhancing Listening Skills: EFL Students' Perceptions - Joko Samudro; M. Zaini Miftah; Zaitun Qamariah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores EFL students’ perceptions of podcasts media used by English teachers in teaching listening comprehension at an Islamic Senior High School in Palangka Raya, Central Kalimantan, Indonesia. Using a case study design, data were collected from 27 tenth-grade students who enrolled in a listening class through questionnaires, semi-structured interviews, observation, and documentation. The quantitative data obtained from the questionnaire were analyzed using descriptive statistical analysis, while data obtained from the interviews, observations, and documentations were analyzed thematically. The findings show that students generally held positive perceptions toward podcasts as learning media in enhancing their listening skills. Despite initial difficulties such as understanding native speakers’ accents, rapid speech, and limited vocabulary, students overcame these challenges using strategies like repetition, subtitles, note-taking, and translation tools. Podcasts were also used to support improvements in pronunciation, vocabulary, and overall listening comprehension. Students also appreciated the flexibility, accessibility, and engaging content that podcasts offer, which enhanced their motivation in learning. However, some obstacles, such as a lack of consistency and motivation, were also reported. Still, students developed adaptive strategies to stay engaged. This study concludes that podcast media can be an effective tool for improving EFL students’ listening skills when integrated with proper guidance and regular practice. The findings highlight the potential of podcasts as a supportive and accessible medium in English language instruction, specifically to foster students' listening skills.